2015
DOI: 10.1128/jb.00349-15
|View full text |Cite
|
Sign up to set email alerts
|

NanI Sialidase, CcpA, and CodY Work Together To Regulate Epsilon Toxin Production by Clostridium perfringens Type D Strain CN3718

Abstract: Clostridium perfringens type D strains are usually associated with diseases of livestock, and their virulence requires the production of epsilon toxin (ETX). We previously showed (J. Li, S. Sayeed, S. Robertson, J. Chen, and B. A. McClane, PLoS Pathog 7:e1002429, 2011, http://dx.doi.org/10.1371/journal.ppat.1002429) that BMC202, a nanI null mutant of type D strain CN3718, produces less ETX than wild-type CN3718 does. The current study proved that the lower ETX production by strain BMC202 is due to nanI gene di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 50 publications
(116 reference statements)
0
29
0
Order By: Relevance
“…However, the NADNA sialidase inhibitor did not inhibit sialidase activity in CN3718 cultures, even at very high doses of the inhibitor. In the presence of NADNA, CN3718 cultures still possessed strong sialidase activity and also made the same amounts of ETX as wild-type CN3718 grown in the absence of any sialidase inhibitor [57]. Collectively, these results suggest that at least some sialidase inhibitors may be potentially useful therapeutics against C. perfringens infections.…”
Section: Sialidase Inhibitors: Potential Therapeutic Agents?mentioning
confidence: 99%
See 4 more Smart Citations
“…However, the NADNA sialidase inhibitor did not inhibit sialidase activity in CN3718 cultures, even at very high doses of the inhibitor. In the presence of NADNA, CN3718 cultures still possessed strong sialidase activity and also made the same amounts of ETX as wild-type CN3718 grown in the absence of any sialidase inhibitor [57]. Collectively, these results suggest that at least some sialidase inhibitors may be potentially useful therapeutics against C. perfringens infections.…”
Section: Sialidase Inhibitors: Potential Therapeutic Agents?mentioning
confidence: 99%
“…Earlier studies demonstrated that NanI production also impacts the production of several C. perfringens toxins [34,37,57]. Specifically, inactivating the nanI gene in C. perfringens type A strain 13 caused a slight increase in supernatant activities of alpha toxin and perfringolysin O (PFO), which are contributors to gas gangrene [37], but their role (if any) in most intestinal infections, particularly human infections, is unsettled [3].…”
Section: Possible Contributions Of Sialidases To C Perfringens Dimentioning
confidence: 99%
See 3 more Smart Citations